Identifying and Prioritizing the Factors Affecting Online Marketing Strategies Based on Competitive Intelligence in Iraqi Telecommunication Companies - AL-Sahlawi, Aziz Sadeq Razzaq; Hosseini, Aboalhasan; Sani, Mohsen Alizadeh; Movaghar , Morteza (Journal of Ecohumanism, 2024)
The business climate is changing quickly and continuously these days due to the advancement of technology and the expansion of global trade. Accordingly, businesses have had to modify their marketing plans to fit this new environment in order to stay competitive, and E-marketing has become a popular alternative. In order to accomplish this, the study will look into the variables influencing internet marketing tactics in the Iraqi telecom sector and rank them according to competitive intelligence. In-depth, semi-structured interviews with 12 academic specialists and marketing managers from Iraqi telecommunications companies were also conducted as part of this study to determine the fundamental elements of competitive intelligence and important internal and external factors influencing online marketing strategies. The researchers employed the Analytic Hierarchy Process (AHP) technique to rank the most important variables identified by the quantitative analysis. The strategic standing of competitors is determined to be the most important external component in internet marketing strategies, based on study findings and expert opinions. Perceived product quality is the most significant internal component of online marketing strategy, according to experts. The most significant sub-criterion in the "competitive intelligence" criterion is "technological intelligence," out of the five sub-criteria. However, the research yields significant information that telecommunication firms in Iraq may utilize to improve their decision-making procedures, allocate resources optimally, and create online marketing strategies that are competitive environment-responsive.